Faktor-Faktor Yang Mempengaruhi Terjadinya Depresi Pascapersalinan - Munisah Munisah; Rahmawati Ika; Luluk Yuliati; Diyana Faricha Hanum (IJMT : Indonesian Journal of Midwifery Today, 2021)
Postpartum is a difficult time for a woman, they experience emotional changes to depression. If postpartum depression is not treated properly, the mother will not be able to take care of the baby and herself. This study aimed to determine the factors which influence postpartum depression in Gresik. The study was an observational analytic with a cohort study approach. The subject was 80 postpartum women. The statistic test used multivariate analysis with multiple linear regression. The result shown the number of postpartum women was 39 people (49%). Adjusted R2 = 70.8% means variable levels of education, work status, family income, family support, self-efficacy, explain postpartum depression variation of 70.8%, and together significantly influenced p <0.001. Conclusion: Education level, employment status, family income, family support, self-efficacy of postpartum mothers are factors that significantly influences the incidence of postpartum depression.